2018
DOI: 10.30631/innovatio.v18i1.40
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Students’ Arabic Proficiency for Vocabulary Mastery in State Islamic Junior High School in Muaro Jambi

Abstract: Mempelajari kosakata berarti menguasai kosakata, terjemahannya, dan penggunaannya dalam kalimat yang benar. Mampu menghafal kosakata tanpa tahu bagaimana menggunakannya dalam percakapan nyata tidak cukup. Dengan demikian, dalam praktiknya, siswa yang sudah memiliki cukup kosa kata diajarkan bagaimana menerapkannya secara tertulis atau lisan. Penelitian ini bertujuan untuk mengetahui bagaimana kosakata diajarkan dan seberapa efektif kosakata itu dalam meningkatkan kemahiran berbahasa Arab siswa di Madrasah Tsan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…Oleh karena itu penulis dengan rendah hati dan dengan dengan tangan terbuka menerima masukan dan kritikan serta saran guna menyempurakan lagi Dalam penulisan selanjutnya. Buska, Wahyudi, Yogia Prihartini, and Nur Hasnah. (2018)…”
Section: Kesimpulanunclassified
“…Oleh karena itu penulis dengan rendah hati dan dengan dengan tangan terbuka menerima masukan dan kritikan serta saran guna menyempurakan lagi Dalam penulisan selanjutnya. Buska, Wahyudi, Yogia Prihartini, and Nur Hasnah. (2018)…”
Section: Kesimpulanunclassified
“…With Frayer model vocabulary graphs, learners are helped to define concepts, goals, or vocabulary and identify and understand new terminology. 8 The Frayer model learning strategy is chosen and used in problem-solving because several advantages are considered such as: (1) Frayer can explore the potential of each individual by utilizing independent learning and (2) the application of Frayer learning model guidance is given individually and in groups with the right level (3) Frayer model LKPD is arranged systematically (4) Frayer model learning is also applied in a short time and routinely in several meetings To shape the ability of students to get used to concentration in learning so that students are motivated in doing tasks, and (5) instil confidence, happiness, and competence as well as the success of students in achieving targets with their abilities and this model can alleviate Some difficulties faced by learners when completing the graphic organizer as well as increasing engagement in learning new words. 9 Among the characteristics of the Frayer model's learning strategy is the emphasis on understanding the concept of the word in a broad context.…”
Section: Introductionmentioning
confidence: 99%
“…Based on research put forward by IIQ in 2018 it stated that 65% of 100% of Muslims in Indonesia were illiterate to the Qur'an (Nira & Fauziyah, 2021). The Central Statistics Agency in its 2020 survey also found that 51.84% of Muslims aged 15 years and over were unable to read or write the Qur'an (Buska et al, 2018). This is also experienced by Islamic Religious Education students at Padang State University who as a whole have not been able to read the Qur'an properly and correctly in accordance with the rules.…”
Section: Introductionmentioning
confidence: 99%